Research methods in librarianship : historical and bibliographical methods in library research - Stevens Rolland E. (London Clive Bingley, 1970)
The present volume includes papers prepared for the third conference on research methods in library science. This conference gave specific attention to historical and bibliographical methods and, like the second conference, eight of the eleven papers were by specialists outside the library field, the remaining three by librarians, library applying the research methods to library problems.
Includes bibliographies and index.
osa 11/02/2019
Loans
Keywords: Library science